Analysis of Myomectomy during Cesarean Section: A Tertiary Center Experience. Issue 1 (2nd January 2022) - Sakinci, Mehmet; Turan, Gokce; Sanhal, Cem Yasar; Yildiz, Yunus; Hamidova, Aygun; Guner, Fatma Ceren; Buyuk, Alime; Dogan, Nasuh Utku; Olgan, Safak
Abstract: Purpose: This study analyzed the safety of myomectomy during the cesarean section (CS). Methods: Pregnant women who underwent myomectomy during CS in a tertiary center between January 2015 and November 2019 were included in the study in Group A, and pregnant women who did not have myoma and who underwent only CS were included in the study in Group B. The following information was obtained from patient files in hospital archives and was then recorded and compared: age, gravidity, parity, gestational week, characteristics of the myomas (i.e., location, size, number, and type), duration of surgery, perioperative complications, need for blood transfusion, preoperative and postoperative hemoglobin (Hb) values, duration of surgery, and hospital stay duration. Results: A total of 83 patients underwent CS plus myomectomy (Group A), and 80 patients (without myoma) underwent only CS (Group B).There were no statistically significant differences between the groups in terms of preoperative and postoperative Hb values or blood transfusion rates ( p > 0.05). Hospitalization and surgery duration were significantly higher in the group that underwent CS myomectomy ( p = 0.001 and p = 0.001, respectively). The mean myoma size was 8.3 ± 4.1 cm in Group A. There was a statistically significant and inverse correlation between the size of the myoma and the delivery week ( p = 0.035). There was a statistically significant and positive correlation between the myoma size and hospital stay ( p = 0.01). Conclusion: Myomectomy during CS is safe and can be applied regardless of the location, size, type, and number of myomas. However, to make myomectomy routine during CS, multi-center studies that include more cases are needed.